2021
DOI: 10.1007/s10570-021-04006-2
|View full text |Cite
|
Sign up to set email alerts
|

Infrared photo-induced force microscopy unveils nanoscale features of Norway spruce fibre wall

Abstract: Infrared photo-induced force microscopy (IR PiFM) was applied for imaging ultrathin sections of Norway spruce (Picea abies) at 800–1885 cm−1 with varying scanning steps from 0.6 to 30 nm. Cell wall sublayers were visualized in the low-resolution mode based on differences in their chemical composition. The spectra from the individual sublayers demonstrated differences in the orientation of cellulose elementary fibrils (EFs) and in the content and structure of lignin. The high-resolution images revealed 5–20 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…Adapted from ref. [111] with permission. (b) AFM Topography and PiFM images at 1658 cm -1 (protein absorption) and 1700 cm -1 (off-resonance) of bacterial cell walls of Enterococcus faecium.…”
Section: S-snom In the Aqueous Phasementioning
confidence: 99%
See 2 more Smart Citations
“…Adapted from ref. [111] with permission. (b) AFM Topography and PiFM images at 1658 cm -1 (protein absorption) and 1700 cm -1 (off-resonance) of bacterial cell walls of Enterococcus faecium.…”
Section: S-snom In the Aqueous Phasementioning
confidence: 99%
“…As an emerging technique with the non-intrusive tapping mode operation, IR PiFM has also been implemented in analyzing biological specimens with nanoscale resolution. For instance, Kesari et al utilized IR PiFM to investigate nanoscale heterogeneities of Norway spruce fiber wall [111]. On the ultrathin sample cross-section of the spruce, different cell wall layers were differentiated based on lignin and cellulose contents, and locations of small cellulose elementary fibrils (EFs) with widths of only 5 -6 nm were identified in PiFM images (Figure 5a).…”
Section: Pifm In Biological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…54,55 In a slightly different area of research, Kesari et al's study of ultrathin microtome sections of Norway Spruce demonstrates the potential of PiFM for visualising the chemical composition of cell walls. 56 Using vibrational bands at 1505, 1471, 1220 and 1145 cm À1 , the distribution of lignin and cellulose was mapped across cell walls, Fig. 10.…”
Section: Biological Surfacesmentioning
confidence: 99%
“…Despite the fact that the primary wall layer is thin and the cellulose amount is very low, because the micro brils in this wall are interwoven randomly, it cannot swell considerably and wraps around the SW unless it is broken apart either by a su cient internal swelling force or by external mechanical action. S1, with 5-20 nm lignin-free voids (Kesari et al 2021), is also very thin, however it has enough cellulose in the form of helical micro brils (50-80° in Norway spruce) to render it highly exible with an enormous expansion capability. Brändström et al (2003) indicated that the S1 layer of Norway spruce is a homogeneous layer oriented approximately perpendicular to the tracheid axis without a cross brillar structure in alternate S (clockwise) and Z (anticlockwise) helices.…”
Section: Optical Microscopymentioning
confidence: 99%